(untitled) (Bangladesh Journal of Nutrition, 2014)
‘Sat Kara’, an important citrus fruit, is edible and popular among the people of greater Sylhet region of Bangladesh as well as Meghalaya and Assam of India. Quantitative biochemical analyzes were conducted to determine its nutritional values through the estimation of proximate nutrients, available major acids and minerals. Results revealed that ash and moisture content of the Satkora peels were 0.89% and 75.53% respectively. Protein, fat and carbohydrates percentage of peels were found to be 1.02%, 0.85% and 18.98% respectively. pH value for peel was 4.32 and, 2.45 for juice. Total Soluble Solid (TSS) for peel and juice • was estimated to be 24.47% and 12.43% respectively. Crude fibre and energy of peel were 2.46% and 90 Kcal per 100 grams. The most important component, vitamin C (ascorbic acid), was found to be 5.58 mg / 100 g for peel and 53.07 mg / 100 g for juice. Citric acid was estimated as 4.53 mg / 100 g for peel and 55.05 mg / 100 g for juice while the values were 1.43 and 4.54, respectively, for malic acid. The respective values for mineral content from peel and juice, as determined according to the standard methods, are; Phosphate: 0.20%,0.14%; Sodium: 3.58%, 2.57%; Potassium: 2.14%, 1.14%; Calcium: 0.19%, 0.21%; Magnesium: 0.38%, 0.26%; Copper: 0.06%, 0.07%; Zinc: 0.07%, 0.05%; Iron: 0.33%, 0.31%; Manganese: 0.13%, 0.17%. Bangladesh J. Nutr. Vol. 26-27, December 2014, P: 53-59